Advances in understanding calcite varve formation: new insights from a dual lake monitoring approach in the southern Baltic lowlands. (9th February 2021) - Roeser, Patricia; Dräger, Nadine; Brykała, Dariusz; Ott, Florian; Pinkerneil, Sylvia; Gierszewski, Piotr; Lindemann, Christin; Plessen, Birgit; Brademann, Brian; Kaszubski, Michał; Fojutowski, Michał; Schwab, Markus J.; et al.
Abstract : We revise the conceptual model of calcite varves and present, for the first time, a dual lake monitoring study in two alkaline lakes providing new insights into the seasonal sedimentation processes forming these varves. The study lakes, Tiefer See in NE Germany and Czechowskie in N Poland, have distinct morphology and bathymetry, and therefore, they are ideal to decipher local effects on seasonal deposition. The monitoring setup in both lakes is largely identical and includes instrumental observation of (i) meteorological parameters, (ii) chemical profiling of the lake water column including water sampling, and (iii) sediment trapping at both bi‐weekly and monthly intervals. We then compare our monitoring data with varve micro‐facies in the sediment record. One main finding is that calcite varves form complex laminae triplets rather than simple couplets as commonly thought. Sedimentation of varve sub‐layers in both lakes is largely dependent on the lake mixing dynamics and results from the same seasonality, commencing with diatom blooms in spring turning into a pulse of calcite precipitation in summer and terminating with a re‐suspension layer in autumn and winter, composed of calcite patches, plant fragments and benthic diatoms. Despite the common seasonal cycle, the share of each of these depositional phases in the total annual sediment yield is different between the lakes. In Lake Tiefer See calcite sedimentation has the highest yields, whereas in Lake Czechowskie, the so far underestimated re‐suspension sub‐layer dominates the sediment accumulation. Even in undisturbed varved sediments, re‐suspended material becomes integrated in the sediment fabric and makes up an important share of calcite varves. Thus, while the biogeochemical lake cycle defines the varves' autochthonous components and micro‐facies, the physical setting plays an important role in determining the varve sub‐layers' proportion.